Lipid-Lowering Therapy Use and Intensification Among United States Veterans Following Myocardial Infarction or Coronary Revascularization Between 2015 and 2019. Issue 12 (14th October 2022) - Zheutlin, Alexander R.; Derington, Catherine G.; Herrick, Jennifer S.; Rosenson, Robert S.; Poudel, Bharat; Safford, Monika M.; Brown, Todd M.; Jackson, Elizabeth A.; Woodward, Mark; Reading, Stephanie; Orroth, Kate; Exter, Jason; et al.
Abstract : Background: Understanding how statins, ezetimibe, and PCSK9i (proprotein convertase subtilisin/kexin type 9 serine protease inhibitors) are prescribed after a myocardial infarction (MI) or elective coronary revascularization may improve lipid-lowering therapy (LLT) intensification and reduce recurrent atherosclerotic cardiovascular disease events. We described the use and intensification of LLT among US veterans who had a MI or elective coronary revascularization between July 24, 2015, and December 9, 2019, within 12 months of hospital discharge. Methods: LLT intensification was defined as increasing statin dose, or initiating a statin, ezetimibe, or a PCSK9i, overall and among those with an LDL-C (low-density lipoprotein cholesterol) ≥ 70 or 100 mg/dL. Poisson regression was used to determine patient characteristics associated with a greater likelihood of LLT intensification following hospitalization for MI or elective coronary revascularization. Results: Among 81 372 index events (mean age, 69.0 years, 2.3% female, mean LDL-C 89.6 mg/dL, 33.8% with LDL-C <70 mg/dL), 39.7% were not taking any LLT, and 22.0%, 37.2%, and 0.6% were taking a low-moderate intensity statin, a high-intensity statin, and ezetimibe, respectively, before MI/coronary revascularization during the study period. Within 14 days, 3 months, and 12 months posthospitalization, 33.3%, 41.9%, and 47.3%, respectively, of veterans received LLT intensification. LLT intensification was most common among veterans taking no LLT (82.5%, n=26 637) before MI/coronary revascularization. Higher baseline LDL-C, having a lipid test, and attending a cardiology visit were each associated with a greater likelihood of LLT intensification, while age ≥ 75 versus <65 years was associated with a lower likelihood of LLT intensification within 12 months posthospitalization. Conclusions: Less than half of veterans received LLT intensification in the year after MI or coronary revascularization suggesting a missed opportunity to reduce atherosclerotic cardiovascular disease risk.